Distinct cytokines balance the development of regulatory T cells and interleukin-10-producing regulatory B cells - Holan, Vladimir; Zajicova, Alena; Javorkova, Eliska; Trosan, Peter; Chudickova, Milada; Pavlikova, Michaela; Krulova, Magdalena (Immunology, 2014)
Regulatory T cells have been well described and the factors regulating their development and function have been identified. Recently, a growing body of evidence has documented the existence of interleukin-10 (IL-10) -producing B cells, which are called regulatory B10 cells. These cells attenuate autoimmune, inflammatory and transplantation reactions, and the main mechanism of their inhibitory action is the production of IL-10. We show that the production of IL-10 by lipopolysaccharide-stimulated B cells is significantly enhanced by IL-12 and interferon-γ and negatively regulated by IL-21 and transforming growth factor-β. In addition, exogenous IL-10 also inhibits B-cell proliferation and the expression of the IL-10 gene in lipopolysaccharide-stimulated B cells. The negative autoregulation of IL-10 production is supported by the observation that the inclusion of anti-IL-10 receptor monoclonal antibody enhances IL-10 production and the proliferation of activated B cells. The effects of cytokines on IL-10 production by B10 cells did not correlate with their effects on B-cell proliferation or on IL-10 production by T cells or macrophages. The cytokine-induced changes in IL-10 production occurred on the level of IL-10 gene expression, as confirmed by increased or decreased IL-10 mRNA expression in the presence of a particular cytokine. The regulatory cytokines modulate the number of IL-10-producing cells rather than augmenting or decreasing the secretion of IL-10 on a single-cell level. Altogether these data show that the production of IL-10 by B cells is under the strict regulatory control of cytokines and that individual cytokines differentially regulate the development and activity of regulatory T cells and IL-10-producing regulatory B cells.
Keywords: buněčná diferenciace; signální transdukce; Signal Transduction; Humans; B cells; messenger RNA; lipopolysacharidy; regulace genové exprese; transformující růstový faktor beta1; cytokiny; Lipopolysaccharides; Female; Interleukin-10; regulační B-lymfocyty; lidé; Recombinant Proteins; Transforming Growth Factor beta1; zvířata; proliferace buněk; myši; Cells, Cultured; B-Lymphocytes, Regulatory; Lymphocyte Activation; myši inbrední C57BL; immunosuppression; Mice; TNF-alfa; rekombinantní proteiny; RNA, Messenger; aktivace lymfocytů; ženské pohlaví; Gene Expression Regulation; homeostáza; Male; cytokines; kultivované buňky; Cell Proliferation; Homeostasis; Cell Differentiation; Mice, Inbred C57BL; Cytokines; regulační T-lymfocyty; interleukin-10 production; interferon gama; Tumor Necrosis Factor-alpha; interleukin-10; Animals; T-Lymphocytes, Regulatory; mužské pohlaví; autoregulation; Interferon-gamma